Enteral nutritional therapy monitoring in icus: a quality indicator? - Aranjues, Ana Luiza; de Castro Teixeir, Ana Carolinaa; Caruso, Lúcia; Garcia Soriano, Francisco (O Mundo da Saúde, 2008)
Nutritional depletion is a frequent condition in patients in Intensive Care Units, (ICUs). At the same time, the parameters of nutritional evaluation have important limitations, making vital the presentation of proposals to favor the quality of care given to these patients. The objective of this study was to monitor Enteral Nutritional Therapy (ENT) in patients in ICUs in two distinct periods and to compare them, aiming at using ENT adequacy as an indicator of care quality. This is a study of a observational prospective character of nutritional offers and intercurrences in patients admitted to adult ICUs with an exclusive ENT for a period of more than 72 hours. We evaluated 30 patients in 2006 and 33 in 2005. The averages of values of energy and proteins calculated, prescribed and administered did not present statistically significant differences. The adequacy calculated/prescribed was next to 100% and the values for the adequacy administered/prescribed were 74% in 2005 and about 80% in 2006. The number of interruptions in ENT infusion in 2006 was 93, having as main cause the procedures, and, amongst these, orotracheal extubation. In 2005, there were 139 pauses, and the main cause was routine interruptions. Results found are consistent to those proposed by literature and indicated the continuity in the quality of the assistance. Following the behavior protocol was vital, and allowed to identify and to adopt strategies regarding ENT interruptions identified in 2005. ENT adequacy percentage is an indicator of quality that we can use for coping with the difficulties in the attainment of other parameters for nutritional evaluation of patients is a severe state.